2013
DOI: 10.1128/aac.02346-12
|View full text |Cite
|
Sign up to set email alerts
|

Phase I, Single-Dose, Dose-Escalating Study of Inhaled Dry Powder Capreomycin: a New Approach to Therapy of Drug-Resistant Tuberculosis

Abstract: dMultidrug-resistant tuberculosis (MDR-TB) threatens global TB control. The lengthy treatment includes one of the injectable drugs kanamycin, amikacin, and capreomycin, usually for the first 6 months. These drugs have potentially serious toxicities, and when given as intramuscular injections, dosing can be painful. Advances in particulate drug delivery have led to the formulation of capreomycin as the first antituberculosis drug available as a microparticle dry powder for inhalation and clinical study. Deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 27 publications
(32 reference statements)
1
66
0
Order By: Relevance
“…Also, as a combined entity, all the above biological functions will influence the rate and extent of drug absorption and retention in the lungs, which determine the bioavailability of the drug. Where understanding the pulmonary drug metabolism comes in, is that the feasible amount of material delivered to the lungs is about 100-150 mg per dose [35], which is in contrast to the gastrointestinal tract, where several grams can be easily administered. Thus, in the presence of a lower level of metabolic enzymes, efflux transporters can still have a significant impact on pulmonary drug delivery compared to the gastrointestinal tract.…”
Section: Transport and Metabolismmentioning
confidence: 99%
“…Also, as a combined entity, all the above biological functions will influence the rate and extent of drug absorption and retention in the lungs, which determine the bioavailability of the drug. Where understanding the pulmonary drug metabolism comes in, is that the feasible amount of material delivered to the lungs is about 100-150 mg per dose [35], which is in contrast to the gastrointestinal tract, where several grams can be easily administered. Thus, in the presence of a lower level of metabolic enzymes, efflux transporters can still have a significant impact on pulmonary drug delivery compared to the gastrointestinal tract.…”
Section: Transport and Metabolismmentioning
confidence: 99%
“…Clinical pharmacokinetic studies in healthy volunteers and diseased population suggest that inhalable antimicrobials are well tolerated and safe for a given dosage regimen [19,[24][25][26][27].…”
Section: Pharmacokinetics Implications Of Inhaled Antimicrobial Therapymentioning
confidence: 98%
“…The aerosol inhalation of kanamycin, an aminoglycoside, was found to be safe in 200 bronchopulmonary suppurative tuberculosis patients [18]. Kanamycin, clofazimine, gentamicin, ofloxacin, streptomycin and neomycin were found to be safe and effective in smaller clinical studies [19][20][21]. Addition of aerosol aminoglycosides to the conventional TB treatment in patients with persistent smear-positive pulmonary tuberculosis turned the TB sputum bacterial culture negative [20].…”
Section: Introductionmentioning
confidence: 95%
“…The use of advanced engineering and formulation tools to allow targeted delivery of anti-tubercular drugs via the pulmonary route has been the focus of many studies worldwide using carriers designed to target the alveolar macrophage [16][17][18][19][20][21][22][23][24]. Our group has showed that Poly(Lactide -co-Glycolide) (PLGA) microparticles encapsulating standard anti-tubercular drugs can be efficiently taken up by THP-1 derived macrophages and cause bacillary killing in an in vitro infection model of tuberculosis [25].…”
Section: Tuberculosis (Tb) Infection Caused By the Pathogen Mycobactmentioning
confidence: 99%